1998
DOI: 10.1002/(sici)1097-0231(19980430)12:8<456::aid-rcm177>3.3.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of spectral reproducibility in direct analysis of bacteria proteins by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry

Abstract: Matrix-assisted laser desorption/ionization (MALDI) time-of-flight mass spectrometry (TOFMS) can be used for rapid detection of bacteria proteins in a crude mixture. It can potentially be used as a tool for bacterial identification based on the mass spectral patterns or the appearance of some characteristic mass peaks. However, there are many experimental parameters that can potentially have a strong effect on the observed mass spectra. The objective of this work is to address the mass spectral reproducibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
150
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(156 citation statements)
references
References 0 publications
5
150
0
1
Order By: Relevance
“…DHB and CHCA are usually optimal for the detection of lower mass ions (Hathout et al, 2000;Williams et al, 2003;Ruelle et al, 2004) with a detection up to 10 kDa when the proper solvent is used. Both SA and FA have been shown to be better for the detection of higher mass ions (above 15 kDa) (Madonna et al, 2000;Conway et al, 2001;Ruelle et al, 2004;Vargha et al, 2006) but provide a lower sensitivity than CHCA (Wang et al, 1998;Ruelle et al, 2004).…”
Section: Techniquementioning
confidence: 99%
See 3 more Smart Citations
“…DHB and CHCA are usually optimal for the detection of lower mass ions (Hathout et al, 2000;Williams et al, 2003;Ruelle et al, 2004) with a detection up to 10 kDa when the proper solvent is used. Both SA and FA have been shown to be better for the detection of higher mass ions (above 15 kDa) (Madonna et al, 2000;Conway et al, 2001;Ruelle et al, 2004;Vargha et al, 2006) but provide a lower sensitivity than CHCA (Wang et al, 1998;Ruelle et al, 2004).…”
Section: Techniquementioning
confidence: 99%
“…Many experimental parameters can have an important effect on the observed mass spectra (Wang et al, 1998). The reproducibility is dependent on the MALDI-TOF instrument, the matrix used, the age of the microorganism, the sample : matrix ratio, the sample concentration, the culture medium and growth conditions (Valentine et al, 2005).…”
Section: Biomarkers Reproducibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the sample preparation strategy adopted for MALDI-TOFMS of whole bacteria is crucial to improve this reproducibility. Indeed, several studies have shown that the obtained bacterial profiles depend on a number of parameters, such as instrumentation, culture media, and bacterial growth [13][14][15][16][17][18].…”
mentioning
confidence: 99%